2017
DOI: 10.1371/journal.pone.0184248
|View full text |Cite
|
Sign up to set email alerts
|

Male-specific association of the FCGR2A His167Arg polymorphism with Kawasaki disease

Abstract: Kawasaki disease (KD) is an acute systemic vasculitis that can potentially cause coronary artery aneurysms in some children. KD occurs approximately 1.5 times more frequently in males than in females. To identify sex-specific genetic variants that are involved in KD pathogenesis in children, we performed a sex-stratified genome-wide association study (GWAS), using the Illumina HumanOmni1-Quad BeadChip data (249 cases and 1,000 controls) and a replication study for the 34 sex-specific candidate SNPs in an indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…Very few studies addressing gene-by-sex interactions at the level of cardio-metabolic phenotypes have been reported (Andreux et al, 2012;Dimas et al, 2012;Liu et al, 2012a;Myers et al, 2014;Rawlik et al, 2016). In general, sex differences in the genetic architecture of human disease (Afshari et al, 2017;Chen et al, 2018;Kwon et al, 2017;Lu et al, 2017) and anthropometric traits (Karp et al, 2017;Kukurba et al, 2016;Nookaew et al, 2013;Palmer and Clegg, 2014;Randall et al, 2013;Weiss et al, 2006;White and Tchoukalova, 2014) are suggested by some studies, yet others failed to find evidence for prevalent sex-specific genetic associations in mouse and human (Krohn et al, 2014). Our results clearly indicate that gene-by-sex interactions are common in mice, at least for metabolic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies addressing gene-by-sex interactions at the level of cardio-metabolic phenotypes have been reported (Andreux et al, 2012;Dimas et al, 2012;Liu et al, 2012a;Myers et al, 2014;Rawlik et al, 2016). In general, sex differences in the genetic architecture of human disease (Afshari et al, 2017;Chen et al, 2018;Kwon et al, 2017;Lu et al, 2017) and anthropometric traits (Karp et al, 2017;Kukurba et al, 2016;Nookaew et al, 2013;Palmer and Clegg, 2014;Randall et al, 2013;Weiss et al, 2006;White and Tchoukalova, 2014) are suggested by some studies, yet others failed to find evidence for prevalent sex-specific genetic associations in mouse and human (Krohn et al, 2014). Our results clearly indicate that gene-by-sex interactions are common in mice, at least for metabolic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Lou and colleagues exhibited nominally reducing tendency for AG þ GG vs. AA and GG vs. AA in their study [26]. While Kwon and colleagues claimed that significant correlation of the polymorphism with KD onset only appeared in males, not among females [29]. Nonetheless, some other researches detected no distinct influence for the polymorphism rs1801274 on KD occurrence at all [20,21,25].…”
Section: Discussionmentioning
confidence: 79%
“…Consequently, in IgG2-mediated phagocytosis, individuals carrying AA genotype would show higher efficiency than those with GG genotype. And altered genotype of the polymorphism rs1801274 could cause insufficient elimination of immune complexes whose depositions on vascular walls might further result in vascular diseases [29]. Besides, earlier reports have suggested potential connection for this polymorphism with some inflammatory diseases and autoimmune diseases, such as systemic lupus erythemathosus, inflammatory bowel disease and rheumatoid arthritis [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first genome‐wide association study (GWAS) for KD, variants of several genes (such as lnx1 , CAMK2D , ZFHX3 , CSMD1 , and tcp1 ) were suggested to be associated with KD susceptibility . In addition, SNPs in rs2254546, rs2857151, rs4813003, rs16921209, rs7922552, rs17076896, rs12068753, rs4786091, and rs2833195 and some SNPs in BLK , CD40 , and FCGR2A may be relevant to susceptibility, clinical presentations (such as CAA and CAL), laboratory data (such as CRP), treatment of KD, and gender in KD in GWASs …”
Section: Discussionmentioning
confidence: 99%